Systemic Lupus Erythematosus Presenting with Status Epilepticus: A Case Report - Faruk İNCECİK and M. Özlem HERGÜNER and Mustafa YILMAZ and Şakir ALTUNBAŞAK (Archives of Rheumatology, 2012)
Systemic lupus erythematosus is an autoimmune disorder involving multiple organs, including the nervous system. Neuropsychiatric involvement in systemic lupus erythematosus is one of the major manifestations of the disease. Both partial and generalised seizures can occur in patients with systemic lupus erythematosus. In this article, we report a seven-year-old girl with a case of systemic lupus erythematosus who initially presented with an episode of status epilepticus.